2016
DOI: 10.1016/j.ultsonch.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron quantification of ultrasound cavitation and bubble dynamics in Al–10Cu melts

Abstract: Knowledge of the kinetics of gas bubble formation and evolution under cavitation conditions in molten alloys is important for the control casting defects such as porosity and dissolved hydrogen. Using in situ synchrotron X-ray radiography, we studied the dynamic behaviour of ultrasonic cavitation gas bubbles in a molten Al-10 wt% Cu alloy. The size distribution, average radius and growth rate of cavitation gas bubbles were quantified under an acoustic intensity of 800 W/cm 2 and a maximum acoustic pressure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(33 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…One of these is ultrasonic vibration or what will henceforth be called Ultrasonic Treatment (UST). It is a mechano‐physical process characterized in this context by low‐amplitude and high‐intensity, where extensive research has shown UST to effectively refine the as‐cast grain structure without using inoculant particles . In fact, one could surmise from this research that UST has considerable potential as a clean, versatile, and efficient technology.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…One of these is ultrasonic vibration or what will henceforth be called Ultrasonic Treatment (UST). It is a mechano‐physical process characterized in this context by low‐amplitude and high‐intensity, where extensive research has shown UST to effectively refine the as‐cast grain structure without using inoculant particles . In fact, one could surmise from this research that UST has considerable potential as a clean, versatile, and efficient technology.…”
Section: Introductionmentioning
confidence: 92%
“…Both cavitation and acoustic streaming significantly affect grain refinement of the solidifying metal . Cavitation is the phenomenon of the formation, pulsation, growth, and implosion of cavities in the liquid phase and at liquid/solid/gas interfaces kinetically. In liquid metals, cavitation is difficult to model and to simulate on a large size scale due to the requirement to solve the coupled fluid flow and nonlinear cavitation equations in a very small time scale, for example, bubble dynamics time scale is in the range of 10 −20 –10 −8 s. Many efforts have been made to model and simulate cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, deagglomerating nanoparticle clusters are of major significance to achieve homogeneous distribution of nanoparticles in the metal matrix. Liquid metal processing assisted by external ultrasound field has been demonstrated to be an efficient way to homogenize the nanoparticle distribution in molten metal [114]. This processing is followed by appropriate solidification, e.g., a sufficiently slow cooling rate [21], which can give rise to homogeneous microstructure in the nanocomposite.…”
Section: Cavitation In Molten Metal-nanoparticle Composite Systemsmentioning
confidence: 99%
“…There are many challenges; one is that liquid metals are usually optically opaque and the majority of metal alloys require relatively high temperature (above a few hundred degrees Celsius) to maintain liquidus structure; special techniques, such as X-ray imaging, are needed to "see" through the liquid metals. In addition, in situ observation requires imaging with nanoscale resolution and extremely high speed (up to on the order of 10 5 frames per second [119]) to be able to capture both activities of nanoparticle clusters and cavitation bubbles (with radii from a few to a few hundreds of micrometers [114,120]). According to the Minnaert equation [121], the critical radius of a cavitation bubble in liquid aluminum is around 60-70 µm when the acoustic pressure is sufficiently high [114].…”
Section: Cavitation In Molten Metal-nanoparticle Composite Systemsmentioning
confidence: 99%
“…UST involves introducing high-intensity ultrasonic waves into liquid metal to induce acoustic cavitation [1]. Cavitation bubbles expand non-linearly, become unstable upon reaching a critical size, and collapse catastrophically, thereby generating high-speed liquid jets, shockwaves, and local hot spots [2][3][4]. Laboratory tests showed that UST offers beneficial effects, such as accelerated diffusion, activation of inclusions, improved wetting, dissolution, deagglomeration, and dispersion of particles leading to degassing, refined, equiaxed solidification microstructure, and uniform distribution of constituent phases [5][6][7][8][9].…”
Section: Investigation Of Acoustic Streaming and Cavitation Intensitymentioning
confidence: 99%